Revisiting the classification of private military and security contractors under international humanitarian law - Mutuma, Kenneth Wyne (Department of Public Law, 2026)
The past two decades have witnessed the emergence and rapid growth of private military and security contractors (PMSCs). Today these corporate entities make up a global security industry based on the provision of security services to both state and non-state clientele across the world whose value is over 100 billion dollars. Although their initial rise was intimately associated with post-Cold War factors and were expected to taper off with the decline of these factors, these speculations have not materialised. Instead, the gap presented by the demand for and supply of security services with the advent of the war on terror has bolstered their growth to the point that the world's leading military power, the United States of America, has become dependent upon these actors. It is not surprising that their rapid rise has sparked enormous interest regarding their activities. In particular the services of PMSCs during armed conflict has generated intense debates on how they should be viewed and treated in this context. These debates have intensified as high profile PMSCs have been forced to submit to the scrutiny of the public because of their use of violence in scenarios that amount to gross violations of human rights and humanitarian law. Even far more significant is the underlying question of the nature of the services they carry out on the battlefield — including services that constitute direct participation in hostilities — and whether the present legal regime governing armed conflict foresees, and adequately caters for, this peculiarity. International humanitarian law classifies all actors operating in armed conflicts as either combatants or civilians, conferring rights and obligations upon them on the basis of where it is that they fall in this divide. To this end, this study relies upon primary and secondary legal materials to outline the current legal regime and ascertain on which side of the dichotomy these actors lie. This study concludes that the majority of PMSC personnel will be considered as civilians, a contradiction of in view of the reality of their activities, and proceeds to make a case for a review of their legal status in the light of certain challenges that arise from their present classification.